The new public management and the application of management indicators in the provincial municipalities of the Macro Region South, 2014 - Samalvides Márquez, Elberth Hernán (2017)
The research was aimed at determining the influence of the new Public Management in the application of management indicators in the Provincial Municipalities of the Macro Region South 2014. Basic type research to 51 managers and officials of the provincial municipal governments of The southern Region of Peru: Apurimac, Arequipa, Moquegua, Tacna, Cusco, Madre de Dios and Puno. lt was determined that: The New Public Management has a significant influence on the application of the indicators of Municipal Management of the Macro Region South 2014 and the evaluation of the new Public Management in the Provincial Municipalities of Macro Region South 2014 is inadequate